Determination and quantification of phenolphthalein found in herbal weight loss products bought from online merchants using high performance liquid chromatography mass spectrometry - Naoe, Angelle Mae L.; Catague, Lui Gen S.
A high performance liquid chromatography-mass spectrometry (HPLC-MS) method was developed and validated for the analysis of phenolphthalein spiked in herbal weight loss supplements purchased from online merchants. HPLC-MS parameters such as mobile phase composition, flow rate, column temperature, gradient elution program, and lens voltage were optimized one parameter at a time. The optimum chromatographic conditions were achieved using a gradient of 2.5 mM ammonium formate: 0.05% formic acid: water buffer as Mobile Phase A and acetonitrile as Mobile Phase B, operated under a 0.35 mL/min flow rate in a column with a 35°C temperature. The lens voltage was set at 0 DL Voltage, -90 Qarray DC, and 52 Qarray RF. The limits of detection and quantitation of the method were 25 ng/mL and 50 ng/mL, respectively. The developed method was linear (R? = 0,9913) with a range of 50-1000 ng/mL. The mean percent recoveries were 98.57 107.35%. Meanwhile, the %RSD of the intra- (n = 3) and inter-day (n =9 for 3 days) precision were 0.94-1.64% and 0.75-1.80%, respectively, signifying that the developed method was accurate and precise. Moreover, matrix and carryover effects were found to be negligible, with matrix effects at 97.76-108.29%. The developed and validated method was used for the analysis of phenolphthalein in 20 herbal weight supplements purchased from two online merchants. Phenolphthalein was detected in 5 samples, with contents ranging from 0.5 196-104.6194 mg/unit. The developed method can be used for the detection or determination of phenolphthalein adulterated into herbal weight loss supplements.